Substantial Inter-Subject Variability in Blood Pressure Responses to Glucose in a Healthy, Non-obese Population - Monnard, Cathriona R.; Fellay, Benoît; Scerri, Isabelle; Grasser, Erik K. (Frontiers in Physiology, 2017)
Aim - A large inter-subject variability in the blood pressure (BP) response to glucose drinks has been reported. However, the underlying factors remain elusive and we hypothesized that accompanying changes in glucose metabolism affect these BP responses. Methods - Cardiovascular and glycemic changes in response to a standard 75g oral-glucose-tolerance-test were investigated in 30 healthy, non-obese males. Continuous cardiovascular monitoring, including beat-to-beat BP, electrocardiographically deduced heart rate and impedance cardiography, was performed during a 30min baseline and continued up to 120min after glucose ingestion. Blood samples were taken at baseline, 30, 60, 90 and 120 min for the assessment of glucose, insulin and c-peptide. Additionally, we evaluated body composition by using validated bioelectrical impedance techniques. Results - Individual overall changes (i.e. averages over 120 min) for systolic BP ranged from -4.9 to +4.7 mmHg, where increases and decreases were equally distributed (50%). Peak changes (i.e. peak averages over 10min intervals) for systolic BP ranged from -1.3 to +9.5 mmHg, where 93% of subjects increased systolic BP above baseline values (similar for diastolic BP) whilst 63% of subjects increased peak systolic BP by more than 4 mmHg. Changes in peak systolic BP were negatively associated with the calculated Matsuda-index of insulin sensitivity (r = -0.39, p = 0.04) but with no other evaluated parameter including body composition. Moreover, besides a trend toward an association between overall changes in systolic BP and total fat mass percentage (r = +0.32, p = 0.09), no association was found between other body composition parameters and overall BP changes. Conclusion – Substantial inter-subject variability in BP changes was observed in a healthy, non-obese subpopulation in response to an oral glucose load. In 63% of subjects, peak systolic BP increased by more than a clinically relevant 4 mmHg. Peak systolic BP changes, but not overall BP changes, correlated with insulin sensitivity, with little influence of body composition.